Bioreducible Carboxymethyl Dextran Nanoparticles for Tumor‐Targeted Drug Delivery. Issue 11 (17th April 2014) - Thambi, Thavasyappan; You, Dong Gil; Han, Hwa Seung; Deepagan, V. G.; Jeon, Sang Min; Suh, Yung Doug; Choi, Ki Young; Kim, Kwangmeyung; Kwon, Ick Chan; Yi, Gi‐Ra; Lee, Jun Young; Lee, Doo Sung; et al.
<x xml:space="preserve">Abstract</x> Bioreducible carboxymethyl dextran (CMD) derivatives are synthesized by the chemical modification of CMD with lithocholic acid (LCA) through a disulfide linkage. The hydrophobic nature of LCA allows the conjugates (CMD‐SS‐LCAs) to form self‐assembled nanoparticles in aqueous conditions. Depending on the degree of LCA substitution, the particle diameters range from 163 to 242 nm. Doxorubicin (DOX), chosen as a model anticancer drug, is effectively encapsulated into the nanoparticles with high loading efficiency (>70%). In vitro optical imaging tests reveal that the fluorescence signal of DOX quenched in the bioreducible nanoparticles is highly recovered in the presence of glutathione (GSH), a tripeptide capable of reducing disulfide bonds in the intracellular compartments. Bioreducible nanoparticles rapidly release DOX when they are incubated with 10 mm GSH, whereas the drug release is greatly retarded in physiological buffer (pH 7.4). DOX‐loaded bioreducible nanoparticles exhibit higher toxicity to SCC7 cancer cells than DOX‐loaded nanoparticles without the disulfide bond. Confocal laser scanning microscopy observation demonstrate that bioreducible nanoparticles can effectively deliver DOX into the nuclei of SCC7 cells. In vivo biodistribution study indicates that Cy5.5‐labeled CMD‐SS‐LCAs selectively accumulate at tumor sites after systemic administration into tumor‐bearing mice. Notably, DOX‐loaded bioreducible nanoparticles exhibit higher antitumor efficacy than reduction‐insensitive control nanoparticles. Overall, it is evident that bioreducible CMD‐SS‐LCA nanoparticles are useful as a drug carrier for cancer therapy.